The moral foundations of trust - Uslaner, Eric M. (Cambridge : Cambridge University Press, 2002)
The Moral Foundations of Trust seeks to explain why people place their faith in strangers, and why doing so matters. Trust is a moral value that does not depend upon personal experience or on interacting with people in civic groups or informal socializing. Instead, we learn to trust from our parents, and trust is stable over long periods of time. Trust depends on an optimistic world view: the world is a good place and we can make it better. Trusting people are more likely to give through charity and volunteering. Trusting societies are more likely to redistribute resources from the rich to the poor. Trust has been in decline in the United States for over 30 years. The roots of this decline are traceable to declining optimism and increasing economic inequality, which Uslaner supports by aggregate time series in the United States and cross-sectional data across market economies.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Trust -- Social aspects; Trust -- Moral and ethical aspects; Social participation; Trust -- United States; Social participation -- United States; Social values -- United States